Incentive-Compatible Long-Term Contracts and Job Rationing - Bester, Helmut (Journal of Labor Economics, 1989)
This article presents a model in which markets for long-term contractual employment coexist with spot markets for labor. Assuming the absence of third-party enforcement, wage contracts are required to be incentive compatible. As a consequence, contract wages yield higher expected utility to the worker than spot-market wages so that, in equilibrium, contractual long-term jobs are rationed.